Spatial variations and determinants of modern contraceptive utilization among sexually active rural women in Ethiopia using mini EDHS 2019 data: spatial and multilevel analysis - Chilot Kassa Mekonnen; Zerko Wako Beko; Gashaw Adane Nega; Hailemichael Kindie Abate (BMC Public Health)
Abstract Background Modern contraceptive prevents unwanted pregnancy and play a paramount role in birth spacing and improving health care costs for the individual, family, community, and the country at large. However, there is limited evidence on the modern contraceptive utilization of rural women in Ethiopia. Hence, this study aimed to assess the spatial distributions and determinants of modern contraceptive utilization of rural women in Ethiopia. Method Data was drawn from the 2019 Ethiopian mini-demographic health survey. Total weighted samples of 5934 mothers who were sexually active in the last five years preceding the survey were included. STATA version 14 was used to clean and analyze the data. The Arc GIS version 10.7 and Sat Scan version 10.1 were used for the spatial analysis to locate hot and cold spot areas in modern family planning among rural Ethiopian women. Multilevel multivariable logistic regression was employed to identify factors associated with modern family planning utilization in Ethiopia. In the multivariable analysis, an adjusted odd ratio with a 95% confidence level indicated a statistical association with the outcome variable at a P- value < 0.05. Result The overall prevalence of modern family planning utilization was 23.00% [95%CI (21.92–24.06)] among reproductive age (15–49) year-old Ethiopian rural women. Those women whose age 25–34 was [AOR = 0.79,95%CI(0.64, 0.98)], age of 35–49 years [AOR = 0.39,95%CI(0.03, 0.49)], being catholic[AOR = 1.46, 95%CI (1.18, 4.03)], not married[AOR = 0.05, 95%CI(0.04, 0.07)], having formal education[AOR = 1.59,95%CI(1.34, 1.88)], being primi-para[AOR = 2.27,95%CI(1.23, 9.33)], being multi-para[AOR = 2.43, 95%CI(1.94, 3.03)], house hold seize 11–24[AOR = 1.89,95%CI(1.38, 4.84)], having sons [AOR = 2.03,95%CI(1.67, 3.84)], having daughters[AOR = 1.55,95%CI(1.19, 2.33)], being middle wealth status[AOR = 1.22,95%CI(1.01, 1.47 )], and having high level community literacy were [AOR = 1.99, 95%CI(1.43, 2.79)] times to utilize modern. In this study, the spatial analysis revealed that SNNPR and Amhara regions have had a high modern contraceptive utilization rate. Whereas, the clusters with low utilization rates were located in Somalia and Afar regions of Ethiopia. Conclusion Less than a quarter of reproductive-age rural women used modern contraceptives in Ethiopia. The study revealed that there were considerable variations in utilizing modern contraceptives across rural areas in the regions of Ethiopia. Hence, the clusters with cold spots shall be emphasized beefing up the services.